Effects of microencapsulated phenethyl isothiocyanate on gastrointestinal cancer cells and pathogenic bacteria - Abrantes, Rafaela (2024)
Gastrointestinal cancers remain a global health burden, demanding more effective prevention and treatments. Phenethyl isothiocyanate (PEITC), a compound derived from cruciferous vegetables, stands out as a promising nutraceutical agent due to its chemopreventive and therapeutic properties. However, its therapeutic translation remains limited mainly due to its poor water solubility and rapid metabolism. Herein, we encapsulated PEITC into biocompatible chitosan-based microparticles with an extra virgin olive oil core to improve its bioavailability and stability. Pure PEITC's biocompatibility and microencapsulated PEITC's stability and antibacterial activity were evaluated. The antibacterial activity analysis showed microencapsulated PEITC as a promising antibacterial agent against gastrointestinal pathogenic bacteria (two Gram-positive and two Gram-negative). The impact of both pure and microencapsulated PEITC was assessed on gastrointestinal cancer cells (MKN45 gastric cancer and SW48 colon cancer cell lines). PEITC exhibited threshold or hormetic dose-dependent toxicity in colon fibroblasts and decreased gastric cancer cells' migration capacity, enhanced upon encapsulation into microparticles. In addition, microencapsulated PEITC induced downregulation of phosphorylated AKT, FAK, and ERK1/2 proteins, disrupting motility signaling pathways and tubulin expression. These findings suggest that the delivery of PEITC via chitosan-based microparticles holds promise as a nutraceutical delivery strategy against gastrointestinal disorders that predispose to cancer.